2014
DOI: 10.2495/wm140091
|View full text |Cite
|
Sign up to set email alerts
|

The physical and chemical properties of solid waste from water tourism. Case study: Taling Chan Floating Market, Bangkok, Thailand

Abstract: Solid waste management represents one of the most challenging and perpetual issues for many developing countries in the world, especially regarding solid waste in important areas such as floating markets. Water tourism is at an ever rapid rate of growth and generates a lot of income into Thailand. The aim of this research is to investigate the physical and chemical properties of solid waste produced by water tourism in Taling Chan Floating Market, Thailand. The results showed five types of waste; food, plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Toxic wastes which are categorized into three as heavy metals (mercury, lead and barium), pesticides (toxaphene, chlordane, lindane) common organic chemicals (benzene, methyl ethyl ketone and chloroform). References [ 19 , 20 ] indicate that Gomez et al analysed household SW for the chemical characteristics and found that SW contains moisture, ash, heavy metals, volatile solid and calorific value. The chemical characteristics of SW are important to assess possible options such as energy content and fusing point of ash in waste processing and waste recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic wastes which are categorized into three as heavy metals (mercury, lead and barium), pesticides (toxaphene, chlordane, lindane) common organic chemicals (benzene, methyl ethyl ketone and chloroform). References [ 19 , 20 ] indicate that Gomez et al analysed household SW for the chemical characteristics and found that SW contains moisture, ash, heavy metals, volatile solid and calorific value. The chemical characteristics of SW are important to assess possible options such as energy content and fusing point of ash in waste processing and waste recovery.…”
Section: Introductionmentioning
confidence: 99%